The The Application Of The Kano Model In Enhancing Digital Learning Satisfaction: A Total Quality Management Perspective - Edy Rakhmadi; Norliani; M. Muhaimin; Aslamiah; Celia Cinantiya (IJGIE (International Journal of Graduate of Islamic Education), 2026)
The transformation of digital learning demands a quality approach that is contextual and student-centered. This article explores the integration of the Kano Model and Total Quality Management (TQM) as a strategic framework for improving the quality of digital learning based on student satisfaction. The Kano Model is employed to classify learning attributes into must-be, one-dimensional, and attractive categories, based on students’ perceptions of various digital learning features. Meanwhile, TQM provides a systemic structure for continuous improvement and stakeholder involvement in quality enhancement processes. This study uses a descriptive qualitative approach, with data collected through Kano-based questionnaires, interviews, and documentation. The results indicate that the Kano Model, when applied in digital learning, enables educators and administrators to classify learning service attributes based on their influence on learner satisfaction, ranging from must-be to one-dimensional to attractive qualities. Meanwhile, TQM provides a comprehensive management foundation that emphasizes continuous improvement, data-driven decision-making, and stakeholder engagement. The combination of both models contributes to building an adaptive, responsive, and learner-centered digital education environment. This integration not only enhances satisfaction but also strengthens institutional competitiveness and quality assurance in the era of digital transformation.